Menumbuhkan Karakter Humanis melalui Aktualisasi Sila Kedua Pancasila dalam Kehidupan Sehari-hari pada Siswa Kelas VI SDN Percobaan - Azkiya, Dhiaul; Pebrianti, As-Sifa; Halmahera, Intan Fajriana Putri; Azizah, Azzahra Nur; Fauziah, Devi Raisa; Jayasti, Shabrina Nazla Ingga; Zaygh, Emir; Ubaidillah, Fajar; Musyaddad, Muhammad Anwar; Idris, Muhammad Iswadi (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
This article discusses the actualization of the second principle of Pancasila, namely "Just and Civilized Humanity," in everyday life, based on the results of a socialization activity conducted for sixth-grade students at SDN Percobaan. The activity aimed to instill humanistic values, strengthen character education, and prevent bullying behavior within the elementary school environment. The method used in this socialization was Participatory Action Research (PAR), which emphasizes active participant involvement in the learning process and collective reflection. The materials presented included an understanding of the second principle of Pancasila, the importance of mutual respect and cooperation, as well as moral value cultivation through contextual approaches appropriate to the students’ developmental stage. The results showed that this participatory approach effectively enhanced students’ understanding of the meaning of the second principle of Pancasila and encouraged the creation of a more inclusive and civilized learning environment. The success of this activity indicates that value and character education can be effectively integrated through communicative and interactive methods at the elementary school level.